A chance to win or lose it all? A systematic literature review on the consequences of natural disasters for governments - Anna Kindsmüller (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2022)
Natural disasters, which usually abruptly cause severe harm and cost lives, have been shown to affect governmental popularity by sometimes leading to additional governmental popularity and sometimes to a loss of popularity. By considering the various theoretical propositions and empirical findings about this nexus together in a systematic review, here we pinpoint which factors determine whether a government gains or loses popularity after a natural disaster. The review shows that a government's operational and symbolic reactions increase the governmental popularity after a natural disaster but suggest that symbolic actions do so more strongly. On the contrary, in a society with significant political knowledge, a government has fewer opportunities to increase their popularity when using only symbolic means or cheap talk.
Keywords: H11; H12; H84; 330; natural disasters; crisis; governmental popularity